High-level workshop on Productive Safety Net Program (PSNP) and economic transformation - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
A half-day high-level workshop on the Productive Safety Net Program (PSNP) and Economic Transformation was co-organized by the Ministry of Agriculture (MoA) and the International Food Policy Research Institute (IFPRI) on October 13, 2025, at Skylight Hotel, Addis Ababa. The event brought together representatives from government institutions and development partners for an insightful and engaging discussion.